Multiple paternity in reproduction of European eel Anguilla anguilla (L. 1758) by artificial mixing of different sperm in equal volumes - Ilaria Guarniero; Daniele Franchini; Alice Ferrari; Laura Gentile; Antonio Casalini; Pietro Emmanuele; Oliviero Mordenti (Aquaculture Reports, 2023)
Because of its complex life cycle and due to multiple stress factors, the European eel is suffering a dramatic decline and has been declared Critically Endangered by the IUCN. A possible way to address this problem could be relieve the pressure on natural stocks by implementing its mass production by artificial breeding protocols. A previous study based on direct observation and parentage assignment underlined the presence of an allegedly hierarchic structure among European eel males in semi-natural mating conditions, with a consequent bias in F1 proportion assigned to each one. The aim of the present study is to attest if a different fertilization protocol based on the artificial mixing of female eggs with different males’ milt in equal volume (1 F:4 M) could represent a solution to the disproportion observed in semi-natural conditions. For this purpose, six families of European eels were generated, and 10 species-specific microsatellite loci were used to infer offspring composition by paternity assignment on 280 samples. Due to the asynchronous ovarian development of female European eels, the percentage of fertilized eggs for each female showed a great variability, ranging from 4.70% to 94.50%. A proportion of 94.02% of genotyped offspring were assigned with high confidence to their true parents. As regard males’ fertilization pattern, no substantial differences from natural mating were observed: a single male accounted for most offspring, which was just mostly composed of full sibs. Concluding, the obtained results suggest that the admixture of an equal volume of different males’ milt seems to contribute to the single-locus genetic variability (observed heterozygosity higher than expected in 7 out 9 loci), but it is not sufficient to ensure all the males the same chance to transmit their gene pool, and new fertilization strategies must be developed.